PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA TENAGA PENDIDIK DI SEKOLAH MENENGAH PERTAMA NEGRI 19 BATANG HARI - Ayu Sumarni; Amiruddin Amiruddin; Beni Setiawan; Zilawati Zilawati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The aim of this research is to analyze the influence of work stress and work motivation on the performance of teaching staff simultaneously and partially at the 19 Batang Hari State Junior High School. This research uses quantitative methods. The population in this sample is all teaching staff at the Batang Hari 19 State Junior High School with 19 teaching staff as respondents. Data collection uses questionnaires and documentation. The results of this research show that: (1). The effect of work stress on the performance of teaching staff is 54%. Calculating tcount shows that tcount = 3.620 ttable= 1.729, this shows that you reject H0 and accept H1. This means that there is a significant influence between the work stress variable on the performance of an educator. (2). The influence of work motivation on the performance of teaching staff is 44.1%. Calculating tcount with ttable shows that tcount = 2.961 ttable= 1.729, this shows that we reject H0 and accept H1. This means that there is a significant influence between work motivation and the performance of teaching staff. (3). The influence of work stress and work motivation on the performance of teaching staff is 82.9%. Calculating Fcount with Ftable gets Fcount =38.730 Ftable= 3.52, this shows that H0 is rejected and H1 is accepted. This means that there is a significant influence between work stress and work motivation simultaneously on the performance of teaching staff.